Identification of novel CA repeat markers for use in fine mapping of the PFHBI gene and screening of the HRC candidate gene - Christoffels, Alan Gilbert (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.M.S.) -- University of Stellenbosch, 1997.